Perception of oral health professionals towards oral health care in children with attention deficit hyperactivity disorder: a cross-sectional questionnaire study - Karmarkar, Sanika U.; Hugar, Shivayogi M.; Badakar, Chandrashekhar M.; Gokhale, Niraj; Bhusari, Bhuvanesh N.; Kadam, Krishna S. (International Journal of Contemporary Pediatrics, 2024)
Background: Attention deficit hyperactivity disorder is one of the most common psychiatric disorders that affects both children and adults and is characterized by inattention, hyperactivity, and impulsivity. Around 9% of worlds’ child population and 20% of India’s is affected by ADHD. A child with ADHD can often have neglected or poor oral hygiene. Attending to the dental treatment of such children can be a challenging task for dentists. The aim of the study was to assess the knowledge, attitude, and practices of oral health care towards children with ADHD among oral health professionals. Methods: The study was carried out among 151 oral health professionals using a validated questionnaire. The results were tabulated in an excel sheet and analysed using SPSS software version 22.0. Results: It was found that among the participants, 71.52% had knowledge scores below the mean knowledge score, while 74.83% had attitude scores below the mean and likewise, 53.64% had practice scores below the mean practice scores. A positive correlation was found between knowledge, attitude, and practice by Karl Pearson’s correlation coefficient with a highly statistically significant p value of 0.0001 (p<0.05). This signified low knowledge correlated with less positive attitude leading to poor practices. Conclusions: Majority of the participating professionals perceive that their training did not prepare them well to treat ADHD affected children. However, practice levels were better among those with more years of experience.